2005
DOI: 10.1046/j.1469-1809.2005.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence Analyses of Human Complement 6 (C6) Gene Suggest Balancing Selection

Abstract: SummaryThe sixth complement component (C6) has a common charge polymorphism, C6A and C6B, with similar gene frequencies in all major populations. In addition, C6B 2 is also found in Japanese populations at a frequency of about 6%. Sequence analyses of the coding region of three human and ape C6 alleles indicated four nonsynonymous and three synonymous changes in C6 * B 2 relative to C6 * A, suggesting that a recombination event occurred between C6 * B 2 and C6 * A to give rise to C6 * B. Sequence variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For example, Tajima's D can become strongly negative when the population has gone through a prolonged bottleneck and expanded thereafter (Sano and Tachida 2005). However, our previous studies suggest that such a severe population bottleneck is unlikely to be the cause (Koda et al 2004;Soejima et al 2005). In addition, the GOF test proposed by Jensen et al (2005) suggested that the original rejection of neutrality in Europeans by the CLR test is more likely to be due to a selective sweep than demography alone.…”
Section: Aim1 Polymorphism 185mentioning
confidence: 87%
“…For example, Tajima's D can become strongly negative when the population has gone through a prolonged bottleneck and expanded thereafter (Sano and Tachida 2005). However, our previous studies suggest that such a severe population bottleneck is unlikely to be the cause (Koda et al 2004;Soejima et al 2005). In addition, the GOF test proposed by Jensen et al (2005) suggested that the original rejection of neutrality in Europeans by the CLR test is more likely to be due to a selective sweep than demography alone.…”
Section: Aim1 Polymorphism 185mentioning
confidence: 87%
“…We also identified a region, characterized by high F ST and low π diff , that contained the complement genes C6 and C7. The complement system plays an important role in innate immunity (58), and our results could indicate that balancing selection is acting in this region of the genome to favor a diverse set of alleles, as is known for C6 in humans (59). Based on the analysis of individual outlier variants, the RIN3 gene showed a consistent pattern of allele frequency differences across all nine of the frog populations sampled in this study, indicating consistent selection in populations distributed across a wide geographic area.…”
Section: Discussionmentioning
confidence: 68%
“…Dobzhansky proposed the ‘balanced hypothesis’, which suggests that many genes are polymorphic and that these polymorphisms are maintained by heterozygote advantage [1]. However, systematic studies that have been carried out on various organisms have so far reported little evidence of balancing selection [28]. …”
Section: Introductionmentioning
confidence: 99%